Cocaine-induced midline destructive lesions - Hanna Pašić; Branka Vidrih; Iva Šarac; Nina Rotim; Ana Hrkać Pustahija; Branko Malojčić; Ivana Karla Franić; Ivona Radmanović; Maja Živković; Stjepan Jurić; Jelena Šarić-Jurić; Marija Bošnjak Pašić (Acta Clinica Croatica)
Prolonged cocaine inhalation can cause destruction of nasal mucosa and ethmoid sinuses and palate perforation, thus inducing cocaine-induced midline destructive lesions (CIMDL) that affect only a limited number of predisposed patients. CIMDL are an autoimmune necrotizing inflammatory phenomenon associated with the presence of atypical antineutrophil cytoplasmic antibody (ANCA). Patients complain of epistaxis, nasal obstruction, hyposmia, sinus infections, and facial pain. Protocol for the CIMDL diagnosis includes medical history, clinical examination, magnetic resonance imaging, laboratory tests, immunology and serology tests, and chest x-ray. A 68-year-old man presented with a brain extension mimicking an ischemic-like lesion with surrounding edema. A diagnosis of CIMDL was made in the light of the patient’s medical history, imaging studies, and laboratory testing including pANCA positivity which seems to promote disease phenotype.